77. Demonstration of stable clusters of symptoms in long COVID. (15th December 2022) - Kenny, Grace; McCann, Kathleen; O'Brien, Conor; Savinelli, Stefano; O'Broin, Cathal; Tinago, Willard; Yousif, Obada; Lambert, John S; Feeney, Eoin; de Barra, Eoghan; Sadlier, Corinna; Landay, Alan; et al.
Abstract: Background: Long COVID is a heterogenous condition. We previously demonstrated distinct phenotypes of long COVID, but the impact of later waves caused by SARS-CoV-2 variants on long COVID presentations has not been described. Table 1 Dates and variants of COVID-19 waves. Methods: We selected individuals with ongoing symptoms > 4 weeks from PCR-confirmed COVID-19 in a multicentre, prospective cohort study. We used multiple correspondence analysis and hierarchical clustering on self-reported symptoms to identify symptom clusters, in individuals recruited during two periods; cohort 1 from March 2020 to April 2021, and cohort 2 from April 2021 to March 2022. We explored differences in symptoms by mapping acute infection to one of four COVID-19 waves in Ireland (table 1) as well as vaccination status, and used Chi2 test to compare symptoms frequencies. Table 2 Patient demographics and differences between the two cohorts. Figure 1 - Heatmaps demonstrating the symptom clusters in the two cohorts Each line represents an individual, red represents the presence of a symptom, blue represents the absence of a symptom. Results: Demographics are shown in Table 2. Cluster analysis of each cohort demonstrated 3 distinct clusters in both cohorts, which shared similar clinical characteristics; a musculoskeletal/pain symptom cluster, a cardiorespiratory cluster and a third less symptomatic cluster (Figure 1). While symptoms within clusters were similar across both periods, in the cardiorespiratory cluster, the frequency of palpitations decreased (56% vs 16%) and cough increased (14% vs 45%) between reporting periods (both P < 0.01). Furthermore, a greater proportion of palpitations were reported in those with COVID-19 from waves 1 and 2 (35% and 28%) compared to 3 and 4 (both 12%, P < 0.001), and a greater proportion of chest pain in waves 1, 2 and 4 compared to wave 3. There were no differences in other symptoms (Table 3). Additionally there were significantly less palpitations reported in those vaccinated at the time of review (17% vs 31% P =0.002), but not chest pain (30% vs 39% P =0.13). In multivariate analysis, infection in wave 3 and 4 but not vaccination status remained significantly associated with lower reported palpitations (OR (95% CI) 0.28 (0.13–0.97) and 0.5 (0.06–0.87) for waves 3 and 4, both P < 0.05), and wave 3 infection remained independently associated with lower reported chest pain (OR 0.3 (0.25–0.7)). Table 3 Proportion of individuals reporting each long COVID symptom depending on timing of acute illness. Conclusion: Three symptom clusters define long COVID across the two cohorts, but characteristics of the cardiorespiratory phenotype have evolved over time with evolution of SARS-CoV-2 variants. Disclosures: All Authors : No reported disclosures.